Robot-assisted video endoscopic inguinal lymphadenectomy for melanoma. Issue 4 (December 2016) - Sánchez, Alexis; Sotelo, Rene; Rodriguez, Omaira; Sánchez, Renata; Rosciano, José; Medina, Luis; Vegas, Liumariel
Abstract Inguinal lymphadenectomy is the indicated procedure in the regional lymph node management for patients with lower limb melanoma and positive nodes. This procedure is commonly associated with surgical site complications. Video endoscopic inguinal lymphadenectomy is a minimally invasive alternative with oncological principles and lower wound-related morbidity. Incorporation of robotic surgery with optimal vision and great maneuverability would offer great advantages. A 42-year-old male patient was diagnosed with acral lentiginous melanoma and palpable inguinal nodes T2 N1 M0. The patient was scheduled for robot-assisted left inguinal video endoscopic lymphadenectomy. The working space is created using blunt-finger dissection and then extended with the endoscope by sweeping with the lens. Two 8-mm robotic trocars and a 10-mm trocar for assistant are placed. The lymphadenectomy is carried out with Maryland and scissors. The operative time was 130 min, estimated blood loss 70 ml and hospital stay 2 days. The robot-assisted inguinal video endoscopic lymphadenectomy is a safe and feasible procedure for lower limb melanoma treatment. The incorporation of the robotic system to this approach where there is a limited working space would offer advantages to the technique.